INTRODUCTION TO PACKAGING LABEL DESIGN TECHNIQUES IN BALINGKA VILLAGE, AGAM REGENCY, WEST SUMATRA PROVINCE - Koja, Reni; Laily, Misbhatul; Azhar, Aulia; Fauzi, Ahmad Zulfikar (Andalasian International Journal of Social and Entrepreneurial Development, 2022)
Background: the activity is carried out with the aim of introducing and training the Balingka village community regarding the design of android-based packaging labels that are suitable for the type of food, so that later they will be able to contribute to increasing the selling power of the product. Method: The packaging label design technique was explained orally by the team of the faculty of agricultural technology, Andalas University to the Balingka village community group while being practiced directly using their respective cellphones. Conclusion: the information conveyed can be implemented by community groups and they are very enthusiastic in the practice of packaging design through cellphones (android-based). Community groups have been able to produce attractive packaging label designs that comply with labeling regulations. Keywords: introduction, technique, packaging, label, design